Prevalence of neuropsychiatric disorders in patients with systemic lupus erythematosus in Pakistan: A systematic review and meta-analysis - Khan, Muhammad Imran; Qureshi, Humera; Akhtar, Sohail; Bae, Suk Joo; Hassan, Fazal (Frontiers in Psychiatry, 2023)
By conducting a systematic review and meta-analysis, we investigated the prevalence of neuropsychiatric (NP) symptoms among systemic lupus erythematosus (SLE) patients in Pakistan. In this review work, three electronic databases (Web of Science, MEDLINE, and Google Scholar) and local databases were screened for twenty years from January 1, 2002 to September 30, 2022, to identify the articles evaluating the prevalence of NP symptoms in SLE patients in Pakistan. We performed a random-effects meta-analysis to estimate the prevalence of NPSLE. Statistical heterogeneity was measured by the I^2 index, and subgroup meta-analyses were used to access the statistical heterogeneity. Furthermore, meta-regression models were used to examine the associations between prevalence estimates and study characteristics of interest. Three independent authors reviewed existing studies, extracted data, and rated the qualities of selected studies. This review was registered on PROSPERO (Registration no. CRD42022361798). Thirteen studies met the inclusion criteria out of the 322 studies with a total of 2003 SLE patients for this systematic review and meta-analysis. The prevalence of NP disorders in SLE patients was estimated to be 30.42% (95% CI:18.26%–44.11%), with cognitive dysfunction being the most common (31.51%; 95% CI:1.28%–76.27%), followed by headache (10.22%; 95% CI: 0.00%–33.43%), seizures (5.96%; 95% CI: 3.80%–8.53%), psychosis (3.64%; 95% CI: 2.38%–5.13%), and neuropathy is the least common (0.86%; 95% CI: 0.00%–2,74%). The heterogeneity between studies was significant (p < 0.01 ). The pooled prevalence of NP disorders among SLE patients was found highest in Punjab (41.21%) and lowest in Sindh (17.60%). Findings from this study revealed that SLE patients have a high prevalence of NP disorders. The most common symptoms were cognitive dysfunctions, headaches, seizures, psychosis, and neuropathy. Clinicians can manage these potentially deadly and disabling diseases more effectively if they understand the incidence of each NP symptom in SLE patients. NP symptoms among SLE patients are at their peak in Pakistan; policymakers should devise preventive strategies to curb the disease.